An assessment on on the technical efficiency of vegetable farming in Marilog District, Davao City - Quiniñeza, Rachel Ann D.
There has been a rapid increase of the population in the Philippines which led to an increase in the demand for demand for food. One of the sources of food is the vegetables. The current demand for vegetables continues, thus, it is necessary to also increase its supply. Hence, it is important to study the factors that have significant impact on the productivity and efficiency of vegetable farming. Consequently, this study aims to assess the technical efficiency of vegetable farmers in Marilog District, Davao City. The study mainly uses primary data which were gathered through cluster sampling. This study utilized the stochastic frontier analysis. The production function was first estimated and the Cobb-Douglas production function was preferred over the Transcendental Logarithmic production function. It was found out that farm area and labor had the largest positive impact on production. On the other hand, for the technical inefficiency effect model, farm experience and tenancy status significantly impact on the efficiency level. Additionally, the mean technical efficiency of vegetable farmers in Marilog District is 67%. It means that the efficiency level of the farmers could still be improved. On the other hand, among the 12 barangays in Marilog District, Brgy. Tamugan had the highest mean technical efficiency. Thus, a model farm should be created in the area which other barangay could replicate.